Synthesis of N6‐Substituted Adenosines as Cytokinin Nucleosides. Issue 1 (2nd April 2018) - Drenichev, Mikhail S.; Oslovsky, Vladimir E.; Tararov, Vitali I.; Mikhailov, Sergey N.
Abstract: This unit describes preparation of N 6 ‐substituted adenosines (cytokinin nucleosides), a unique class of compounds with a wide spectrum of biological activities. Regioselective alkylation of N 6 ‐acetyl‐2′, 3′, 5′‐tri‐ O ‐acetyladenosine with alkyl halides under basic conditions or alcohols under Mitsunobu conditions followed by deprotection are the methods of choice for the preparation of the cytokinin nucleosides. The attractive feature of this strategy is the possibility of using a broad library of commercially available alkyl halides and alcohols under mild reaction conditions. © 2018 by John Wiley & Sons, Inc.